2023
DOI: 10.3390/ani13050873
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Function, Biometrics, and Echotextural Attributes in Santa Inês Ewes Superovulated with Different Total Doses of Porcine Follicle-Stimulating Hormone

Abstract: Premature regression of corpora lutea (PRCL) may adversely affect the outcome of hormonal ovarian superstimulation in small ruminants, and the total dose of exogenous gonadotropins used may be one of the causes of this condition. There were two major objectives of the present study: (1) to evaluate the effects of different superovulatory doses of porcine follicle-stimulating hormone (pFSH) on the biometry, blood perfusion (Doppler), and echotextural characteristics of luteal structures; and, (2) to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Granulosa cells are important in follicular development and atresia. Apoptosis of granulosa cells is closely associated with follicular atresia ( Wang et al, 2023 ), process controlled by reproductive hormones and cytokines ( Santos et al, 2022 ; Bevilaqua et al, 2023 ; Grynberg et al, 2023 ; Li et al, 2023 ). Numerous studies performed in chicken, rodents and pigs have shown that proapoptotic and antiapoptotic factors contribute to follicular atresia triggering the apoptosis of granulosa cells ( Guo et al, 2019 ; Han et al, 2023 ; Ludwig et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Granulosa cells are important in follicular development and atresia. Apoptosis of granulosa cells is closely associated with follicular atresia ( Wang et al, 2023 ), process controlled by reproductive hormones and cytokines ( Santos et al, 2022 ; Bevilaqua et al, 2023 ; Grynberg et al, 2023 ; Li et al, 2023 ). Numerous studies performed in chicken, rodents and pigs have shown that proapoptotic and antiapoptotic factors contribute to follicular atresia triggering the apoptosis of granulosa cells ( Guo et al, 2019 ; Han et al, 2023 ; Ludwig et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%